Psychological barriers to climate-friendly food choices - Elzarie Theron; Hagen, Sean (PINS-Psychology in Society, 2023)
The food supply chain is a significant contributor to climate change. By following a climate-friendly diet, consumers have the potential to significantly reduce the effects of climate change. However, despite the growing awareness of the climate-friendly food options that are available, consumers still choose foods with a high carbon footprint. Following a survey design, this study aimed to determine the extent to which four psychological processes (denial, conflicting goals and aspirations, tokenism, and interpersonal influence) limited climate-friendly food choices in a sample of adult consumers residing in Gauteng, South Africa. Data were collected from 146 participants using the Climate-friendly Food Choices Scale and the Psychological Barriers Scale. Results indicated that, overall, the barriers were negatively associated with climate-friendly food choices. Regression analysis indicated that the four psychological barriers explained 10.6 % of the variance in climate-friendly food choices. Conflicting goals and aspirations and denial were identified as the two main psychological barriers to climatefriendly food choices. It is therefore essential to consider the psychological processes that could have a limiting effect on the adoption of climate-friendly food choices in our approach to encourage pro-environmental change.